The muscle fiber type-fiber size paradox: hypertrophy or oxidative metabolism? - van Wessel, T.; de Haan, A.; van der Laarse, W. J.; Jaspers, R. T. (European Journal of Applied Physiology, 2010)
An inverse relationship exists between striated muscle fiber size and its oxidative capacity. This relationship implies that muscle fibers, which are triggered to simultaneously increase their mass/strength (hypertrophy) and fatigue resistance (oxidative capacity), increase these properties (strength or fatigue resistance) to a lesser extent compared to fibers increasing either of these alone. Muscle fiber size and oxidative capacity are determined by the balance between myofibrillar protein synthesis, mitochondrial biosynthesis and degradation. New experimental data and an inventory of critical stimuli and state of activation of the signaling pathways involved in regulating contractile and metabolic protein turnover reveal: (1) higher capacity for protein synthesis in high compared to low oxidative fibers; (2) competition between signaling pathways for synthesis of myofibrillar proteins and proteins associated with oxidative metabolism; i.e., increased mitochondrial biogenesis via AMP-activated protein kinase attenuates the rate of protein synthesis; (3) relatively higher expression levels of E3-ligases and proteasome-mediated protein degradation in high oxidative fibers. These observations could explain the fiber type-fiber size paradox that despite the high capacity for protein synthesis in high oxidative fibers, these fibers remain relatively small. However, it remains challenging to understand the mechanisms by which contractile activity, mechanical loading, cellular energy status and cellular oxygen tension affect regulation of fiber size. Therefore, one needs to know the relative contribution of the signaling pathways to protein turnover in high and low oxidative fibers. The outcome and ideas presented are relevant to optimizing treatment and training in the fields of sports, cardiology, oncology, pulmonology and rehabilitation medicine.